Strategi Peningkatan Literasi Budaya dan Kewarganegaraan Pembaca dalam Lingkup Perpustakaan Akademik - Sanjiwani, Ketut Ayu (Jurnal Ilmiah Widya Sosiopolitika, 2025)
Academic libraries are not only information centers, but also play a strategic role in increasing the cultural literacy and citizenship of readers. This literacy is important to understand cultural values, tolerance, and rights and responsibilities as citizens. This research aims to explore library strategies in improving cultural literacy and citizenship through literature study methods. The results of the discussion identified a number of strategies, such as the provision of relevant collections, the implementation of educational programs, cultural exhibitions, and digital literacy training. In addition, libraries can create multicultural collaborative spaces, collaborate with cultural institutions, increase the role of librarians, and integrate cultural and citizen literacy in the academic curriculum. By adopting this strategy, libraries can encourage readers to play an active role in creating an inclusive, tolerant, and globally insightful society. This effort strengthens the library's function as a learning center, cultural preservation, and community empowerment.